2020
DOI: 10.1002/ijc.33433
|View full text |Cite
|
Sign up to set email alerts
|

Missing and decayed teeth, oral hygiene and dental staining in relation to esophageal cancer risk: ESCCAPE case‐control study in Kilimanjaro, Tanzania

Abstract: In the African esophageal squamous cell carcinoma (ESCC) corridor, recent work from Kenya found increased ESCC risk associated with poor oral health, including an ill‐understood association with dental fluorosis. We examined these associations in a Tanzanian study, which included examination of potential biases influencing the latter association. This age and sex frequency‐matched case‐control study included 310 ESCC cases and 313 hospital visitor/patient controls. Exposures included self‐reported oral hygiene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 34 publications
2
47
4
Order By: Relevance
“…Furthermore, two recent case-control studies from East Africa have shown that dental fluorosis, an irreversible hypo-mineralization of the tooth enamel characterized by brown stains and pits in severe cases, may be an important understudied risk factor contributing to ESCC risk in this high-risk region. Moderate/severe dental fluorosis was strongly associated with ESCC risk (compared with no dental fluorosis) with an OR of 14.7 (95% confidence interval (CI): 7.6–28.6) [ 76 ] and 13.5 (95% CI: 5.7–31.9) [ 85 ] in case-control studies from Kenya and Tanzania, respectively. The large effect sizes and consistent observations across these two independent studies warrant further investigations to assess how dental fluorosis may impact ESCC risk.…”
Section: Epidemiology Of Ecmentioning
confidence: 99%
“…Furthermore, two recent case-control studies from East Africa have shown that dental fluorosis, an irreversible hypo-mineralization of the tooth enamel characterized by brown stains and pits in severe cases, may be an important understudied risk factor contributing to ESCC risk in this high-risk region. Moderate/severe dental fluorosis was strongly associated with ESCC risk (compared with no dental fluorosis) with an OR of 14.7 (95% confidence interval (CI): 7.6–28.6) [ 76 ] and 13.5 (95% CI: 5.7–31.9) [ 85 ] in case-control studies from Kenya and Tanzania, respectively. The large effect sizes and consistent observations across these two independent studies warrant further investigations to assess how dental fluorosis may impact ESCC risk.…”
Section: Epidemiology Of Ecmentioning
confidence: 99%
“…Other inherent limitations of the case‐control study design include the possibility of control selection bias and misclassification of the exposure status, as already mentioned, in particular the under‐reporting of geophagia. Strengths of the study are a large ESCC study which has already led to the identification of several risk factors 5‐7 . Further, the potential selection bias when recruiting from a capital city tertiary hospital—of hospital controls residing nearby while cases originate from afar—was minimized.…”
Section: Discussionmentioning
confidence: 99%
“…Strengths of the study are a large ESCC study which has already led to the identification of several risk factors. 5 , 6 , 7 Further, the potential selection bias when recruiting from a capital city tertiary hospital—of hospital controls residing nearby while cases originate from afar—was minimized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from Asia, Europe, Latin America, Kenya, and Iran have reported associations of ESCC with poor oral hygiene, chronic periodontal disease, dental decay, and tooth loss (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Recently, three parallel case-control studies in Kenya and Tanzania, conducted as part of the African Esophageal Cancer Consortium (AfrECC) and ESCCAPE (esccape.iarc.fr) collaborations, reported possible associations of poor or infrequent oral hygiene with increased risk for ESCC in East Africa (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%